FINANCIAL LITERACY AND LEGAL AWARENESS FOR BETTER FINANCIAL DECISION: A PUBLICATIONS TRENDS - Suziraha Dzulkepli; Shariah Bagam Abdul Rahman; Mohd Afiq Ab Jalil (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2024)
This bibliometric analysis explores the evolving trends in research on financial literacy and legal awareness, and their role in improving financial decision-making. The importance of these topics has grown significantly as individuals face increasingly complex financial decisions, underscoring the need for both financial education and legal knowledge. However, despite their importance, there is a lack of comprehensive studies that examine the global research landscape on this subject. To address this gap, the study employs Scopus Analyzer and VOSviewer software to analyze a dataset of 1706 publications. The analysis identifies key themes, popular keywords, and patterns of co-authorship collaboration across different countries. Results reveal a strong emphasis on financial literacy, legal knowledge, and their combined influence on financial security and decision-making processes. Furthermore, a notable trend in international collaboration emerges, with multiple countries working together to deepen the understanding of these critical issues. The findings suggest that research in this area is growing, with a clear shift towards interdisciplinary approaches that integrate legal and financial domains. The study concludes by highlighting the importance of continued research in this field and encourages further exploration into the intersection of financial literacy and legal awareness as crucial factors for enhancing financial decision-making globally.